Therapeutic impact of red blood cell transfusion on anemic outpatients: the RETRO study. Issue 6 (18th March 2019) - St. Lezin, Elizabeth; Karafin, Matthew S.; Bruhn, Roberta; Chowdhury, Dhuly; Qu, Lirong; Bialkowski, Walter; Merenda, Scott; D'Andrea, Pamela; McCalla, Anne‐Lyne; Anderson, Lisa; Keating, Sheila M.; Stone, Mars; et al.
Abstract : BACKGROUND: Patients with cancer or other diagnoses associated with chronic anemia often receive red blood cell (RBC) transfusion as outpatients, but the effect of transfusion on functional status is not well demonstrated. STUDY DESIGN AND METHODS: To estimate the effect of transfusion on functional status and quality of life, we measured 6‐minute walk test distance and fatigue‐ and dyspnea‐related quality‐of‐life scores before and 1 week after RBC transfusion in 208 outpatients age ≥50 with at least one benign or malignant hematology/oncology diagnosis. To account for potential confounding effects of cancer treatment, patients were classified into two groups based on cancer treatment within 4 weeks of the study transfusion. Minimum clinically important improvements over baseline were 20 meters in walk test distance, 3 points in fatigue score, and 2 points in dyspnea score. RESULTS: The median improvement in unadjusted walk test distance was 20 meters overall and 30 meters in patients not receiving recent cancer treatment. Fatigue scores improved overall by a median of 3 points and by 4 points in patients without cancer treatment. There was no clinically important change in dyspnea scores. In multiple linear regression analysis, patients who maintained hemoglobin (Hb) levels of 8 g/dL or greater at 1 week posttransfusion, who had not received recent cancer treatment, and who did not require hospitalization during the study showed clinically important increases in mean walk test distance. CONCLUSIONS: Red blood cell transfusion is associated with a modest, but clinically important improvement in walk test distance and fatigue score outcomes in adult hematology/oncology outpatients. Abstract : See editorial on page 1887–1890, in this issue